Intratumor Epigenetic Heterogeneity—A Panel Gene Methylation Study in Thyroid Cancer - Zhu, Chaofan; Zhang, Meiying; Wang, Qian; Jen, Jin; Liu, Baoguo; Guo, Mingzhou (Frontiers in Genetics, 2021)
Background: Thyroid cancer (TC) represents the most common endocrine malignancy, accounting for 3.4% of all cancers diagnosed annually. Standard therapy with surgical resection and radioactive iodine ablation fails in about 10% of differentiated thyroid cancer and all anaplastic thyroid carcinoma (ATC). A better understanding of the molecular mechanisms underlying thyroid cancer progression may be the key to tailor the management of this disease. Epigenetic heterogeneity in thyroid cancer remains unclear. Methods: A total of 405 surgical resected thyroid cancer samples were employed (three spatially-isolated specimens were obtained from different regions of the same tumor). Twenty-four genes were selected as discovery group, and frequently methylated genes in thyroid cancer were designed as validation group. Gene promoter region methylation was examined by Methylation specific PCR (MSP). Results: Five genes (AP2, CDH1, DACT2, HIN1 and RASSF1A) were found frequently methylated (>30%) in thyroid cancer. The five genes panel was designed as validation group for further epigenetic heterogeneity analysis. AP2 methylation is associated to gender (p<0.05), DACT2 methylation is associated to age, gender and tumor size (all p<0.05), HIN1 methylation is associated to tumor size (p<0.05) and extra-thyroidal extension (p<0.01). RASSF1A methylation is associated to lymph node metastasis (p<0.01). For heterogeneity analysis, AP2 methylation heterogeneity was associated to tumor size (p<0.01), CDH1 methylation heterogeneity is associated to lymph node metastasis (p<0.05), DACT2 methylation heterogeneity was associated to tumor size (p<0.01), HIN1 methylation heterogeneity was associated to tumor size and extra-thyroidal extension (all p<0.01). Conclusion: Five of twenty-four genes were found frequently methylated in human thyroid cancer. Based on 5 genes panel analysis, epigenetic heterogeneity is an universal event. Epigenetic heterogeneity is associated to cancer development and progression.